Virtual Reality as a method to reduce pain and anxiety in pediatric patients - a review - Fussek-Styga, Urszula; Błaszczyk, Agnieszka; Trojan, Sara; Kwieciński, Jakub; Miszuda, Sławomir; Szwedkowicz, Agata; Basiaga, Bartosz; Bednarz, Krzysztof; Heluszka, Jakub; Leśniak, Marek (Journal of Education, Health and Sport, 2023)
Introduction and purpose The role of virtual reality (VR) is increasingly being discussed not only in the context of entertainment, but also in the medical field. Recently, there has been a growing number of literature analyzing its effect on reducing pain and anxiety, which are common problems of pediatric patients. These feelings can negatively affect their psyche, health recovery, but also doctor-patient cooperation and avoidance of treatment in the future.The purpose of this study is to analyze and summarize the potential of using virtual reality to reduce pain and anxiety in pediatric patients. Material and methods A literature review of 2015-2022 based on PubMed and Google Scholar. Results The literature reviewed shows the extensive use of virtual reality in the treatment of pain and anxiety in pediatric patients. VR is a good method for reducing perioperative anxiety, pain during wound care and pain as well as anxiety in invasive procedures. This method may not be beneficial in the treatment of acute pain and its role is uncertain during dental treatment. Disadvantages of this technique include the need for financial investment in equipment and trained staff. Patients may experience dizziness and motion sickness during its use. Another disadvantage is also that it does not provide a long-term analgesic effect. Conclusion There appears to be merit in using this technology as an adjunctive method to reduce pain and anxiety in pediatric patients. There is also a need for further research in this area and the development of appropriate therapeutic intervention for a specific age group and procedure in a well-defined process by a trained team.